2016
DOI: 10.4236/jwarp.2016.813096
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Physicochemical and Microbiological Parameters of a Teaching Hospital’s Wastewaters in Abidjan in Côte d’Ivoire

Abstract: This work deals with the physicochemical and microbiological characterization of a hospital wastewater that is directly discharged in water bodies without treatment. Our focus was paid on the teaching hospital of Treichville (Cote d'Ivoire). For the purpose, various physicochemical parameters such as temperature, pH, dissolved oxygen, total dissolved solid, conductivity, nitrate, phosphate, chloride, chemical oxygen demand (COD), biological oxygen demand for five days (BOD 5), salinity, and total suspended sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…found that the values of nitrate, dissolved oxygen demand, COD, BOD5 and biological parameters of teaching hospital wastewaters did not respect the international (WHO) values recommended for the water to be discharged in the environment [25]. In this study, the average suspended matter content (96.17 mg/L) obtained also exceeded the limit value of the WHO standards (20 mg/L) for discharges of wastewater [12].…”
Section: Physico-chemical Qualitymentioning
confidence: 54%
“…found that the values of nitrate, dissolved oxygen demand, COD, BOD5 and biological parameters of teaching hospital wastewaters did not respect the international (WHO) values recommended for the water to be discharged in the environment [25]. In this study, the average suspended matter content (96.17 mg/L) obtained also exceeded the limit value of the WHO standards (20 mg/L) for discharges of wastewater [12].…”
Section: Physico-chemical Qualitymentioning
confidence: 54%
“…Because of the importance of temperature in the physico-chemical analysis and treatment of wastewaters [8,[49][50][51], the effect of temperature on paracetamol oxidation process was also studied in this work. Figure 14(a) presents the obtained results, showing that increase of temperature promotes paracetamol oxidation.…”
Section: A D V a N C E D O N L I N E A R T I C L Ementioning
confidence: 99%
“…The intensive use of paracetamol leads to its presence in the environment, and more specifically in the surrounding waters. This makes a real problem for humans and other living things, since paracetamol breaks down into very toxic metabolites [5][6][7][8]. A general awareness is therefore necessary in order to propose effective methods for detection, quantification and decontaminating wastewaters containing paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…The wastewater containing pharmaceutical effluents can be carried out by various processes, including physicochemical and biological treatments, which are currently well controlled at laboratory scale and applied on a large scale in industry [4,9,10]. In this context, several recent advances in the treatment by oxidation of organic contaminants contained in aqueous effluents have been made.…”
Section: Introductionmentioning
confidence: 99%